(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
This paper explored the area of digital activism with a focus on the narratives of girls as exemplified in Bana Alabed’s memoir, Dear World. The world is experiencing an era where online platforms serve as powerful avenues for self-expression and advocacy. This study aimed to explore how young girls utilize digital spaces to share their stories, thereby amplifying their voices, and engaging in activism. The research employed a qualitative approach, analyzing the content of Bana Alabed’s Dear World to understand the experiences and expressions of the girls in War-Torn Syria. By examining the varied dimensions of digital activism, the paper sought to unravel the impact of these virtual platforms on shaping narratives among young girls who are facing adversity. Through an in-depth analysis of the text and drawing on the Post-Colonial Feminist theoretical framework, the research aimed to contribute to the understanding of the connectedness between digital activism and the empowerment of girls. The findings of this study provided more knowledge about the ways in which technology can serve as a tool for engendering social change and amplifying the voices of marginalized individuals, especially girls.